Distribución y Abastecimiento de Agua para riego presurizado en el ámbito del Proyecto Especial Chavimochic. 2023 - Pastor Vera, Miguel Angel. (2023)
The Board of Pressurized Irrigation Users of the Moche Virú Chao Irrigation District, is a non-profit Civil Association that, according to Law 29338 (Water Resources Law), has the purpose of managing the proper use of water resources in the scope of the new areas of CHAVIMOCHIC Irrigation as part of the agro-industrial development of our users. Likewise, its purpose is to achieve the active and permanent participation of the water users of its territorial jurisdiction in the operation and maintenance of the irrigation and drainage infrastructure, as well as in the development, conservation, preservation and efficient use of the water resource in accordance with the provisions issued by the Local Water Authority, in accordance with the General Water Law, its Regulations, Supreme Decree No. 057-2000-AG and other legal provisions in force. In the area of Distribution and Water Supply, irrigation and cultivation plans are contemplated, flow requirements for irrigation of companies (users), monitoring of delivery flows from the Santa River, water balance depending on the type of crop and water need. that it needs according to the campaign, consumption controls carried out (volumetric data), inspection of new areas that request the right to use water. In addition to supplying according to water flows for pressurized irrigation in the CThe Board of Pressurized Irrigation Users of the Moche Virú Chao Irrigation District, is a non-profit Civil Association that, according to Law 29338 (Water Resources Law), has the purpose of managing the proper use of water resources in the scope of the new areas of CHAVIMOCHIC Irrigation as part of the agro-industrial development of our users. Likewise, its purpose is to achieve the active and permanent participation of the water users of its territorial jurisdiction in the operation and maintenance of the irrigation and drainage infrastructure, as well as in the development, conservation, preservation and efficient use of the water resource in accordance with the provisions issued by the Local Water Authority, in accordance with the General Water Law, its Regulations, Supreme Decree No. 057-2000-AG and other legal provisions in force. In the area of Distribution and Water Supply, irrigation and cultivation plans are contemplated, flow requirements for irrigation of companies (users), monitoring of delivery flows from the Santa River, water balance depending on the type of crop and water need. that it needs according to the campaign, consumption controls carried out (volumetric data), inspection of new areas that request the right to use water. In addition to supplying according to water flows for pressurized irrigation in the Chavimochic area of irrigation sectors I, II, III, IV and V whose users are duly registered and that correspond to a directorial resolution for a water use license approved by ANA., in addition to delivering water with the quality established in the JURP, promoting improvements in automating the processes of water collection and delivery. chavimochic area of irrigation sectors I, II, III, IV and V whose users are duly registered and that correspond to a directorial resolution for a water use license approved by ANA., in addition to delivering water with the quality established in the JURP, promoting improvements in automating the processes of water collection and delivery.